The Relationship Between Young Amateur Footballers' Ego States and Accordance Levels Based on Their Positions In The Team and Their Performance: Samsun Province Sample - Fatih Samet Atasoy; Soner Çankaya (Selcuk University, 2020)
The aim of this thesis was to investigate the relationship between ego states based on Transactional Analysis (TA) and accordance levels based on team positions of footballers playing in elite U-19 young amateur league in Samsun province and their performance. The sample of the study consisted of 183 amateur football players playing in the league. For this purpose, TA Ego Status Scale, Personal Information Form and Performance Evaluation Scale were used as data collection instruments. One-way ANOVA and Tukey HSD test were used to examine the differences among the total scores of the players' ego states (Critical Parent, Nurturing Parent, Adult, Natural/Free Child and Adapted Child) for the various variables (the football players' positions on pitch, their performance etc). In addition to this, the correlation between the ego status (observed) of football players and ego status of their positions (expected) was estimated by using Pearson correlation coefficient. The results showed that the correlation between amateur team players' ego status based on transactional analysis and their positions in the team were only positively correlated with the adult ego status; however no statistically significant relationship was found between performance of football players and their ego status. In conclusion, unlike the results of studies showing that athletes' personality traits and psychological skills affect their sporting performance, this result of this study are in parallel with the results of studies which showed no a important correlation between athletes' personality traits and their sporting performance. For this reason, it is necessary to do more studies that different research methods and scales should be used on different sample groups in teams and individual sports based on TA Ego States.